Removal of heavy metals from water using carbon nanotubes functionalized with deep eutectic solvents / Mohamed Khalid Mohamed Saied - Mohamed Khalid, Mohamed Saied (2017)
Heavy metal pollution in water and wastewater is the cause of major environmental and industrial concern. Carbon nanotubes (CNTs) have proved to be sophisticated adsorbents to remove heavy metals, but require functionalization with non-environmental friendly acids and chemicals through complicated processes. Herein, we present the use of a novel functionalization agent for CNTs, namely deep eutectic solvents (DESs) or, in other words, analogous ionic liquids. Because of their capability as novel solvents in chemistry, DESs were recently involved in a variety of applications. The DESs were prepared using different molar ratios of hydrogen bond donors (HBDs) to salts. The characteristic physical properties of the DESs, specifically freezing point, density, viscosity, electrical conductivity and surface tension, were investigated with respect to temperature. In addition, the functional groups associated with the syntheses of DESs were analyzed utilizing FTIR spectroscopy. Subsequently, the selected DESs were used as functionalization agents with pristine CNTs to form novel adsorbents for the removal of lead ions (Pb2+), arsenic ions (As3+), and mercury ions (Hg2+) from water. Furthermore, the DESs were applied to pre-oxidized CNTs with KMnO4, and pre-acidified CNTs, with HNO3 and H2SO4, respectively. The adsorbents were characterized using Raman, FTIR, XRD, FESEM, EDX, BET surface area, TGA, TEM, and Zeta potential. A screening process was conducted for each heavy metal to select the best adsorbent, with highest removal, of a particular DES-CNTs combination. Response surface methodology was used to optimize the removal conditions for each adsorbent. Isotherm and kinetics studies were performed for each selected adsorbent. The optimization study showed that the optimum conditions for Pb2+ removal were pH 5 with adsorbent dosage of 5 mg and a contact time of 15 min. The maximum adsorption capacity (qmax) of the selected adsorbent (KTEG-CNTs) for Pb2+ was 288.4 mg/g and the experimental data fitted well to both Langmuir and Freundlich isotherms models. The removal of Hg2+ was successful with two adsorbents specifically, KA-CNTs and KT-CNTs. First, the experimental qmax was 186.97 mg/g using the phosphonium based DES-functionalized CNTs and the Freundlich isotherm model. The optimum removal conditions were pH 5.5, a contact time 28 min, and an adsorbent dosage of 5 mg. Secondly, by using an ammonium based DES as functionalization agent, Langmuir and Freundlich isotherms models described the absorption of Hg2+ with acceptable accuracy and the qmax was 177.76 mg/g. The optimum removal conditions were pH 6.4, an adsorbent dosage of 6.0 mg, and a contact time of 45 min. Adsorption of As3+ was achieved using three CNTs-DES combinations selected based on the previously described screening study. When using an ammonium based DES to functionalize CNTs, the qmax was 17 mg/g. Meanwhile, with phosphonium based DESs the qmax reached 23.4 mg/g. The optimum removal conditions for As3+ adsorbents were found to be at a contact time of 55 min, an adsorbent dosage of 20 mg, and pH of 6.0 and 3.0. The adsorption kinetics rates for all adsorbents were described well by a pseudosecond-order kinetics model and the Langmuir isotherm model described the adsorption isotherm.